Pattern of paediatric trauma in Sokoto, North West Nigeria - Muhammad Oboirien (Wolters Kluwer Medknow Publications, 2013)
Background: Paediatric trauma has become a major cause of mortality, disability and socioeconomic burden in developing countries and the World Health Organization (WHO) projects that by 2020 it will be the leading disease globally. This study described the pattern of paediatric injuries seen at a regional trauma center in North West, Nigeria. Settings and Design: Trauma centre of a tertiary hospital in North-Western Nigeria. Materials and Methods: A retrospective look at the trauma register for records of paediatric trauma from January to December 2010 was performed. Information obtained include age and sex, causes and pattern of injury. The limit of 16 years was set for paediatric in our centre. Results: The numbers of paediatric trauma seen over the 12-month period were 567 out of a total of 3984 trauma cases representing 14.2%. The number of males was 407(71.8%) and females were 160(28.2%) with M: F ratio of 2.5:1. The mean age was 7.77 and standard deviation of 0.19. Road Traffic Accidents (RTA) and Domestic injuries representing 44.8 and 42.0%, respectively, were the commonest causes of injuries. Laceration and bruises, head injuries including extremities were the commonest types of injuries seen. Conclusion: Road traffic accidents and domestic injuries as common causes of paediatric trauma need to be 'addressed by the authorities' so as to reduce the burden of trauma on the vulnerable children in our society.